Estudio comparativo del desarrollo del lenguaje en niños de 24 a 30 meses según nivel educativo de los padres, en el distrito de Anta, Región Cusco - Quispe Rojas, Ilce Tongshi (2024)
The main objective of the study was to compare the development of language in children aged 24 to 30 months, users of non-school Early Education Programs (PRONOEI), according to the educational level of their parents in the district of Anta, Cusco region, being the study population 35 children of this age group. The research adopted a quantitative approach, collecting relevant data and using statistical tests to validate the hypothesis, descriptive-comparative type with a non-experimental design with cross-sectional cut, analyzing data from two groups. The MacArthur Test was used to assess the children's language development and a questionnaire was used to collect the parents' educational level. Data processing included descriptive and inferential statistical analysis with SPSS and Excel. The descriptive results suggest greater language development in children with parents who have higher education; however, the inferential analysis does not confirm these statistically significant differences as a function of the parents' educational level. It is concluded that other factors not considered, such as socioeconomic environment, access to additional educational resources, parenting style and time spent interacting with children, could influence language development. The results support superior progress in the development of vocalizations, words and grammar in children whose parents have secondary or higher education. It is concluded that linguistic stimulation provided by parents and social interactions play an important role in language development, regardless of parental educational level. This study indicates that child language development is influenced by a combination of factors beyond parental educational level.